Essays on water resources management in the agricultural sector of South Africa: the role of technology, policy and institutions in mitigating farm level water scarcity - Apio, Alfred Tunyire (School of Economics, 2024)
South Africa is a water-stressed country prone to multi-year droughts and water shortages, with varying impacts on several sectors, including agriculture. Agriculture, as the largest user of the country's freshwater resources, is the most sensitive sector to water scarcity and would be the hardest hit by intensifying climate change, droughts, and water shortages. Yet the agricultural sector has the largest potential to make adjustments and take actions to promote resilience to water scarcity by implementing water conservation, water quality regulation, legitimate allocation, and an appropriate management response in the face of growing water scarcity. This thesis, therefore, provides an understanding of how the agricultural sector of South Africa is responding to the water scarcity problem. Its general objective is to further the stock of knowledge in natural resources management, with special emphasis on water resources management in the agricultural sector. It consists of three core chapters (chapters 2, 3, and 4), alongside the introduction (chapter 1) and conclusion (chapter 5). The first core chapter (Chapter 2) examines the factors that drive farmers' multiple adoption of six water conservation practices (WCPs) and the intensity of their adoption. Using survey data from 555 farmers in the Limpopo River Basin (LRB) of South Africa, a multivariate probit model is estimated to determine these factors, and for the intensity of their adoption, an ordered probit model is estimated. The results show that gender, age, education, and farm size, among other factors, influence the probability and extent of adoption of WCPs. Furthermore, combinations like drip and/or sprinkler irrigations and cover cropping, drip and/or sprinkler irrigations, and intercropping, among other practices, are complements, suggesting the bundling of these WCPs. This chapter provides a clear framework in agriculture not only to prepare farmers to be resilient in the midst of intensifying climate change, droughts, and water shortages but also to enhance their water conservation efforts. This would help farmers become better acclimatized to the growing realities of water scarcity and enhance the sustainability of the resource, enabling them to continue to make meaningful contributions to economic growth. The second core chapter (Chapter 3) employs a discrete choice methodology to investigate farmers' willingness to accept compensation to control agricultural nonpoint source (agNPS) pollution in the LRB. The LRB is highly polluted, yet it is important for agriculture, mining, and industry, which contribute to employment, income, and poverty alleviation. Reducing this pollution is part of the restoration and protection plan for the basin. However, because agNPS pollution does not easily lend itself to traditional forms of regulation, monetary incentives that induce farmers to adjust their farming practices to reduce agriculture's impact on water quality are seen as an effective means of controlling it, hence this chapter. Conditional logit and restricted latent class models are used to estimate the survey data of 552 farmers. This chapter identified one random choice class and three preference classes of farmers (low, moderate, and high resistance) with dissimilar compensation requirements to improve water quality. The chapter offers new insights to enrich the efficient design of tailored water quality improvementrelated agri-environmental schemes for more persistent environmental benefits that would ultimately result in positive externalities beyond benefits to farmers and the environment. The third core chapter (Chapter 4) presents a meta-analysis of the empirical literature that investigates the performance of water institutions. This chapter synthesized and quantified the overall water institution-performance effect using data extracted from 23 original studies that reported the effect of water institutions on the performance of the water sector in various regions of the world. The results from the bivariate and multivariate meta-regressions suggest the presence of a publication selection bias that favours a positive impact of water institutions on performance. Also, a genuine positive empirical effect of water institutions on the performance of the water sector is found. In addition, the variations in the primary studies are attributable to differences in the way the primary studies capture water institutions, the dependent variables used to capture performance, and the estimation strategy/methodology, among others. The main novelty of this chapter is its use of meta-analysis to increase the statistical power of this set of literature, which covers different methodologies, geographic and environmental conditions under which water institutions performed compared to single studies. This thesis concludes by underscoring forcefully that farmers need sustainable supplies of water but must also manage the impact of agriculture on water resources to ensure sufficient quantity and quality of water for production, but robust water management institutions are key. In terms of policy recommendations, this thesis offers several of them, including but not limited to the fact that WCPs are interdependent, and therefore, the design of any effective strategy(ies) aimed at increasing their uptake rate must take this interdependence into consideration. It also advocates the promotion and use of monetary incentives to induce farmers to lessen agriculture's impact on water quality. Finally, it recommends that to engender water sector reforms and/or for the further development, facilitation, and strengthening of water institutions, there is the need to incorporate and strengthen the water law and/or the water policy in policy formulation and reforms for successful water resource management and governance.